Panel Data Analysis to Identify The Relationship Between Human Capital, Social Capital and the Possibility of Community Income Decline in Indonesia Big Cities - Bagus Pambudi; Deni Amelia; Pandu Adi Cakranegara; Musdirwan; Abdurohim (SEULANGA SYSTEM PUBLISHER, 2024)
This study aims to empirically evaluate the importance of social capital on the likelihood of falling into poverty. The expanded survey employs user-based research, focusing on the household unit of analysis. The results of the analysis seem to confirm the hypothesis that social ties have the potential to reduce poverty. In this context, it is important to differentiate the impact of social capital in the context of survival and mobility. The results of this study tend to support a subsistence effect of social capital rather than a mobility effect. This shows that social capital itself is still not an effective enough instrument to reduce the risk of falling into poverty. However, realizing the positive role of social capital in promoting upward socio-economic mobility requires considering its interaction with family human capital, reinforcing the notion that social capital alone is insufficient to combat social segregation. In this context, coexistence, characterized by enormous diversity in the content and quality of social contacts, appears to play a role in the formation of social capital. Underlying social issues need to be considered. If this is a reality, it is important to establish policies aimed at restoring the construction processes between various social ties to achieve greater sociocultural diversity within each network formed. While different alternative strategies can achieve policy objectives, this research does not address the potential impact of combining educational and spatial integration policies to counteract educational segmentation and urban segregation.